1989
DOI: 10.1056/nejm198906013202205
|View full text |Cite
|
Sign up to set email alerts
|

Human Immunodeficiency Virus Type 1 Infection in Homosexual Men Who Remain Seronegative for Prolonged Periods

Abstract: Infection with the human immunodeficiency virus type 1 (HIV-1), as demonstrated by viral cultures, has been described in some patients before antibodies to HIV-1 can be detected, but the duration and frequency of such latent infections are uncertain. We selected prospectively a cohort of 133 seronegative homosexual men who continued to be involved in high-risk sexual activity, and we cultured 225 samples of their peripheral-blood lymphocytes, using mitogen stimulation to activate the integrated HIV-1 genome. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
108
0
8

Year Published

1989
1989
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(120 citation statements)
references
References 26 publications
4
108
0
8
Order By: Relevance
“…A study on the impact of helminthes on the response to immunization in pregnant women and children in Uganda has shown that infection with helminthes has suppressive effects on the immune response (Elliott et al 2007). General immune suppression in MSM would be another example, and in that population a very long WP has been reported (Imagawa et al 1989;Gupta et al 1992). Viral genotypes and clades (Andersson et al 2005), social and environmental factors, and genetics, could also play a role in determining the HIV WP.…”
Section: Potential Causes and Effectors Of The Length Of The Wpmentioning
confidence: 98%
“…A study on the impact of helminthes on the response to immunization in pregnant women and children in Uganda has shown that infection with helminthes has suppressive effects on the immune response (Elliott et al 2007). General immune suppression in MSM would be another example, and in that population a very long WP has been reported (Imagawa et al 1989;Gupta et al 1992). Viral genotypes and clades (Andersson et al 2005), social and environmental factors, and genetics, could also play a role in determining the HIV WP.…”
Section: Potential Causes and Effectors Of The Length Of The Wpmentioning
confidence: 98%
“…Subjects enjoyed taking the interview, thought it was a good method for screening donors, and trsted the confidentiality of the interview. Donors Furthermore, a recent study has raised the possibility that the rate of seronegativity among HIV-infected high-risk gay males ("false negatives") may be much higher than previously recognized [4]. Such findings underscore the importance of obtaining accurate information from prospective donors.…”
mentioning
confidence: 99%
“…Although there are 3,345 cases of transfusion-associated AIDS in the United States, excluding haemophiliacs (Center for Disease Control, Atlanta, April 30,1990) and 226 in Canada, 27 since the implementation of HIV-1 screening there have been only 14 cases of transfusion-associated AIDS in the United States. 2~ The National Office of the Canadian Red Cross Society is aware of two possible HIV seroconversions associated with transfusions (personal communication, National Office, Canadian Red Cross Society).…”
Section: Human Immunodeficiency Virus (Hiv) Infectionmentioning
confidence: 99%